Inaugural HealthAccord Conference (SportAccord Convention, Bangkok, Thailand): The Power of Sport — The Power to Change. Issue 8 (August 2018) - Pitsiladis, Yannis P.; Carty, Catherine; Ferriani, Ivo; Lewis, Sarah; Vitello, Matteo; Crooks, Charmaine; Liljelund, John; Loroupe, Tegla; Eades, David; Mountjoy, Margo; Pigozzi, Fabio
Abstract : SportAccord organized the inaugural HealthAccord conference on April 19, 2018, in Bangkok, Thailand. The goal of HealthAccord is for the International Sport Federations (IF) and sport industry leaders to address high-priority issues facing sport through a serious commitment to innovation to protect athlete health, to enhance athlete performance, and to stimulate action to improve global health through the promotion of physical activity. The first HeathAccord conference was organized by drawing on the knowledge and experience of experts from global health programs focused on athletes and global citizens, respectively. The first session, "The Power of Sport, " addressed the application of "state of the art" sport science and sport medicine for the protection of athlete health and to enhance sport performance. "The Power of Sport" session concentrated on enabling athletes to perform spectacular feats that are "higher, stronger, faster" intended to engage and thrill global audiences without resorting to prohibited substances and methods, to enable athletes to remain active in sport for a longer career, and to increase the attraction of sport for sponsors. In the second session, "The Power to Change, " sport was viewed as having an important role in promoting physical activity within their respective federations, community, and internationally. The Olympic movement, IF, and other sport stakeholders are urgently needed to become the social drivers to correct the mismatch between physical activity for health development and draw toward sedentary lifestyles of the modern world. Key outcomes of this first HealthAccord conference were the agreement among participants to develop an innovative and high-impact collaboration between IF and related stakeholders; to use sport as a social movement platform to measurably improve health, both for athletes and for global citizens.